การสร้างความหมายโดยใช้สัตว์เป็นสัญลักษณ์ในวรรณกรรมฮาวทู (How-to books) เรื่อง ถ้าโลกมันแย่ก็แค่คิดแบบคาปิบาร่า: Meaning-Making Through Animal Symbolism in the How-to Book Think Like a Happybara - Lai, Yang; ยาดี สุภาวดี (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
This article aims to examine meaning-making through animal symbolism in the how-to book Think Like a Happybara. The study employs a qualitative approach using textual analysis of five chapters, based on concepts of meaning, symbolism, and animal characters. The findings indicate that the capybara is used as a symbolic figure to convey life philosophies, including calmness, peaceful coexistence, stress-free living, acceptance of change, and adaptability. The use of animal symbolism enables readers to easily access life-related concepts and reflects the role of how-to literature in contemporary society.